A Prospective US National Trauma Center Study of Firearm Injury Survivors Weapon Carriage and Posttraumatic Stress Disorder Symptoms. Issue 4 (October 2021) - Nehra, Deepika; Bulger, Eileen M.; Maier, Ronald V.; Moloney, Kathleen E.; Russo, Joan; Wang, Jin; Anderson, Kristina; Zatzick, Douglas F.
Abstract : Objective: To describe the demographic, injury-related, and mental health characteristics of firearm injury patients and trace firearm weapon carriage and PTSD symptoms over the year after injury. Summary and Background Data: Based on the increasing incidence of firearm injury and need for novel injury prevention strategies, hospital-based violence intervention programs are being implemented in US trauma centers. There is limited data on the long-term outcomes and risk behaviors of firearm injury survivors to guide this work. Methods: We conducted a secondary analysis of a pragmatic 25-trauma center randomized trial (N = 635). Baseline characteristics of firearm-injured patients (N = 128) were compared with other trauma patients. Mixed model regression was used to identify risk factors for postinjury firearm weapon carriage and PTSD symptoms. Results: Firearm injury patients were younger and more likely to be black, male and of lower socioeconomic status, and more likely to carry a firearm in the year before injury. Relative to preinjury, there was a significant drop in firearm weapon carriage at 3- and 6-months postinjury, followed by a return to preinjury levels at 12-months. Firearm injury was significantly and independently associated with an increased risk of postinjury firearm weapon carriage [relative risk = 2.08, 95% confidence interval (1.34, 3.22), P < 0.01] and higher PTSD symptom levels [Beta = 3.82, 95% confidence interval (1.29, 6.35), P < 0.01]. Conclusions: Firearm injury survivors are at risk for firearm carriage and high PTSD symptom levels postinjury. The significant decrease in the high-risk behavior of firearm weapon carriage at 3–6 months postinjury suggests that there is an important postinjury "teachable moment" that should be targeted with preventive interventions. Trial Registration: ClinicalTrials.gov NCT02655354